ANALYSIS OF INSTRUCTIONAL MATERIAL BASED ON ENGLISH FOR SPECIFIC PURPOSES ON THE NEEDS OF MANAGEMENT STUDENTS AT STIE TRI DHARMA NUSANTARA - Syamsinar Syamsinar; Marwah Juwita Yusuf (Universitas Muhammadiyah Makassar, 2019)
The difficulty of finding textbooks that fit the needs of students in Management studies makes researchers interested in analysing English material for teaching at the tertiary level. Needs analysis is the first step in developing and improving teaching materials and improving learning activities. In addition, needs analysis is very effective in evaluating students' needs in relation to English for academic, specific, and general purpose. Musdalifa and Syarifuddin (2017) state that needs analysis is very important and as a guideline for designing syllabi, subject matter, and class activities. This study is entitled